Right atrial diameter and outcome of catheter ablation of atrial fibrillation - Wen, Song -Nan; Liu, Nian; Bai, Rong; Tang, Ri-Bo; Yu, Rong-Hui; Long, De-Yong; Sang, Cai-Hua; Jiang, Chen-Xi; Li, Song-Nan; Wu, Jia-Hui; Ruan, Yan-Fei; Hu, Rong; et al. (Journal of interventional cardiac electrophysiology, 2017)
Purpose While AF is considered more like a left atrial (LA) disease, to what extent the right atrium contributes to the pathogenesis and ablation outcome of AF remains unclear. This study aimed to identify if right atrial diameter (RAD) could predict arrhythmia recurrence after catheter ablation of atrial fibrillation (AF). Methods Four hundred and seventy patients with drug-resistant AF [paroxysmal AF (PAF) 196; non-PAF 274] who underwent primary catheter ablation were enrolled. Ablation strategy included complete bilateral pulmonary vein isolation (PVI) in all patients and additional linear ablation across mitral isthmus, LA roof, and tricuspid isthmus in non-PAF cases. Risk factors associated with recurrence were determined by a Cox regression model, and the predictive power was evaluated by using receiver operating characteristic curve. Results After 24.3 ± 18.0 months, 284 patients (60.6%) experienced atrial tachyarrhythmia recurrence (111 in PAF, 173 in non-PAF). RAD was moderately associated with LA diameter ( r = 0.371, P < 0.001), left ventricular ejection fraction ( r = −0.205, P < 0.001), and left ventricular end-diastolic diameter ( r = 0.319, P < 0.001). Multivariate Cox regression analysis demonstrated that RAD was an independent predictor for recurrence only in PAF patients with LAD ≥35 mm (HR 1.044, 95% CI 1.007–1.082, P = 0.021). The RAD cutoff value of 35.5 mm predicts atrial tachyarrhythmia recurrence with 85.4% sensitivity and 29.2% specificity. Kaplan-Meier analysis indicated that RAD over 35.5 mm is associated with more recurrence after PAF ablation (log-rank P = 0.034), comparing to those with RAD <35.5 mm. Conclusions RAD predicts outcome of ablation only in patients with PAF and concurrent LA enlargement. Under this condition, RAD <35.5 mm is associated with a more favorable recurrence-free survival at over 2-year follow-up.